Interannual variability of rainfall in Malaysia - Lim, You Rang (Universiti Putra Malaysia, 2011)
This study addresses (a) the advance and retreat of the NE monsoon, (b) the climatic variability in East Malaysia, and (c) the hourly rainfall distribution in Peninsula Malaysia. Data from 27 principle meteorological stations ranging from 1964 to 1998 has been employed. The result of this investigation shows that the advance of the NE monsoon starts in November and retreats in January over Peninsula Malaysia. On the other hand, The NE monsoon season arrives in East Malaysia at the end of October. It retreats from East Malaysia in March.